2019
DOI: 10.1002/humu.23944
|View full text |Cite
|
Sign up to set email alerts
|

Whole MYBPC3 NGS sequencing as a molecular strategy to improve the efficiency of molecular diagnosis of patients with hypertrophic cardiomyopathy

Abstract: Hypertrophic cardiomyopathy (HCM) is the most common heritable cardiomyopathy, historically believed to affect 1 of 500 people. MYBPC3 pathogenic variations are the most frequent cause of familial HCM and more than 90% of them introduce a premature termination codon. The current study aims to determine the prevalence of deep intronic MYBPC3 pathogenic variations that could lead to splice mutations. To improve molecular diagnosis, a nextgeneration sequencing (NGS) workflow based on whole MYBPC3 sequencing of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…The detection of new variations in hypertrophic cardiomyopathy not only provides a new understanding of the pathophysiology of hypertrophic cardiomyopathy but also plays an important role in the clinical treatment and prognosis of patients with hypertrophic cardiomyopathy and their families by early and even pre-symptomatic intervention. 23,24 MYBPC3 polymorphisms have also been implicated in sudden infant death syndrome. 25 However, further research is needed to explore the functional analysis of the detected MYBPC3 variants by using induced pluripotent stem cells to elucidate phenotypical differences.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of new variations in hypertrophic cardiomyopathy not only provides a new understanding of the pathophysiology of hypertrophic cardiomyopathy but also plays an important role in the clinical treatment and prognosis of patients with hypertrophic cardiomyopathy and their families by early and even pre-symptomatic intervention. 23,24 MYBPC3 polymorphisms have also been implicated in sudden infant death syndrome. 25 However, further research is needed to explore the functional analysis of the detected MYBPC3 variants by using induced pluripotent stem cells to elucidate phenotypical differences.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on such variants in cardiomyopathies are still limited in number, but suggest that deep-intronic variation may contribute substantially to the disease burden. For example, WGS identified pathogenic variants in 9% of a selected subset of patients (with HCM/left-ventricular hypertrophy/surgical interventions/family history of HCM) in which the genetic cause was elusive [8] and deep-intronic variants in MYBPC3 alone are estimated to explain 6.5% of HCM cases [93].…”
Section: Exome Vs Genome Sequencing: 2% Vs 100%mentioning
confidence: 99%
“…Of note, our ability to interpret these types of variants is still limited and hampered by the lack of public catalogues of clinically classified non-coding variants, although efforts to characterize the effect of noncoding variants at the genome-wide level are being carried out [94]. Currently, definitive interpretation of deep-intronic or regulatory variation requires RNA as well as DNA sequencing to investigate the effects of such variants on splicing patterns or gene expression levels [8,93,95], with access to myocardial tissue rarely available for routine genetic testing. However, in the near future WGS will plausibly be employed by a larger number of laboratories thanks to the combination of lower costs and more accessible informatics infrastructure.…”
Section: Exome Vs Genome Sequencing: 2% Vs 100%mentioning
confidence: 99%
“…Particularly in the last four years, cryptic splice-altering MYBPC3 variants located in proximal, intermediate or distal intronic positions relative to the nearest splice site 14 19 , and also in exonic sequences 17 , 20 , have been increasingly recognized as a cause of HCM. Accordingly, it was suggested that massively parallel sequencing of the whole MYBPC3 gene, including the complete sequence of introns, improves the yield and efficiency of molecular diagnosis of patients with HCM 15 , 16 , 19 . Usually, rare MYBPC3 intronic variants that could be detected by massively parallel sequencing of a patient’s genomic DNA are prioritized for functional validation using deep-learning in silico splicing tools 17 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 99%